STUDI AWAL ENERGI TERMAL PADA TOSAN AJI - Amos Setiadi (Institut Seni Indonesia Surakarta, 2022)
The existence of thermal energy in Tosan Aji recorded with a measuring instrument with an image output (visual) is one learning medium that helps the sense of view. In a Tosan Aji made of iron and steel, metal materials and prestige materials are believed to be stored thermal energy suspected to be a store when creating and forging materials, and other techniques have not been revealed. In the process, heat transfer occurs, called heat transfer, which can be analyzed from engineering disciplines that learn how to generate heat, use heat, change heat, and move heat. Tosan Aji thermal measurements using FLIR Infrared Camera instrument is an infrared camera whose results show images/visualization of thermal gradations of objects caught by the camera. With the method of treatment in the absence of conduction, convection, radiation, and the thermal condition of space, Tosan Aji has a thermal condition of 31.3 to 34.0 degrees Celsius. Unlike other metal objects, sickle and lower crowbar. Thermal distribution on blades and blades in “warangka” is different.